Final answer:
To find the inverse function, we interchange x and y, solve for y, and express y in terms of x. Hence, f^-1(x) is equal to 1/(x - 2).
Step-by-step explanation:
- First, we substitute y for f(x), so the equation becomes y = (2x + 1)/x.
- Next, we interchange x and y to obtain x = (2y + 1)/y.
- To find the inverse, we solve for y: xy = 2y + 1. Distribute xy to get xy = 2y + 1.
- Now, isolate y by subtracting 2y from both sides: xy - 2y = 1.
- Factor out y: y(x - 2) = 1.
- Divide both sides by (x - 2) to solve for y: y = 1/(x - 2).
- Therefore, the inverse function is f^-1(x) = 1/(x - 2).